Low risk of neurodevelopmental impairment among perinatally acquired HIV‐infected preschool children who received early antiretroviral treatment in Thailand. Issue 4 (16th April 2019) - Jantarabenjakul, Watsamon; Chonchaiya, Weerasak; Puthanakit, Thanyawee; Theerawit, Tuangtip; Payapanon, Jesdaporn; Sophonphan, Jiratchaya; Veeravigom, Montida; Jahanshad, Neda; Thompson, Paul M; Ananworanich, Jintanat; Malee, Kathleen; Pancharoen, Chitsanu; et al.
Abstract: Introduction: Antiretroviral therapy (ART) is recommended in perinatally HIV‐infected (PHIV) infants immediately upon diagnosis. We aimed to compare neurodevelopmental outcomes between PHIV children who initiated ART within 12 months of life and perinatally HIV‐exposed uninfected (PHEU) children and to assess neurodevelopmental outcomes by timing of ART. Methods: This prospective cohort study included Thai children aged 12 to 56 months who were assessed with the Mullen Scales of Early Learning (MSEL) at enrolment and at 48 weeks. Global Developmental Impairment (GDI) was defined as Early Learning Composite (ELC) ≤ 70 on the MSEL; typical developmental pattern was defined as ELC > 70 at both visits. Logistic regression was used to compare prevalence of any GDI. Predictors of changing ELC scores were analysed with generalized estimating equations linear regression model. Results: From 2016 to 2017, 50 PHIV (twenty‐seven early ART within three months and twenty‐three standard ART within three to twelve months) and 100 PHEU children were enrolled. Median (IQR) age at first assessment was 28 (19 to 41) months. PHIV children had lower age‐relevant Z scores for weight, height and head circumference compared to the PHEU group ( p < 0.05). The prevalence of overall GDI was 18% (95% CI 11 to 27) and 32% (95% CI 20 to 47) in PHEU and PHIV children respectively ( p = 0.06). In subgroup analysis, 22% (95% CI 9 to 42) of early ART PHIV children and 44% (95% CI 23 to 66) of standard ART PHIV children had overall GDI. There was a higher rate of GDI in standard ART PHIV children ( p = 0.01), but not in the early ART group ( p = 0.62) when compared with PHEU children. The standard ART PHIV group demonstrated lower typical developmental pattern than both the early ART PHIV group and the PHEU group (57% vs. 77% vs. 82% respectively). Non‐attendance at nursery school was associated with changes in ELC score during study participation (adjusted coefficient −3.8; 95% CI −6.1 to −1.6, p = 0.001). Conclusions: Preschool children with HIV who initiated ART in the first three months of life had a similar rate of GDI as PHEU children. Lack of nursery school attendance predicted poor developmental trajectory outcomes among PHIV children.